On the optimality of price-posting in rental markets - Juan Beccuti (University of Bern, Department of Economics, 2020)
This paper considers a multi-period setting where a monopolist, with short-term commitment, rents one unit of a durable good to a single consumer in every period. The consumer's valuation constitutes his private information and remains constant over time. By using a mechanism design approach, the paper shows that the optimal renting strategy is to offer a simple price in every period. Although sophisticated mechanisms can make separation feasible when price-posting cannot achieve it, this happens precisely when separation is dominated by pooling. Moreover, the monopolist's choice of whether to discriminate or not depends on a simple and apparently myopic rule, reminiscent of its static equivalent.
Keywords: D82; D86; D42; 330; Durable good; renting; dynamic adverse selection; mechanism design; short-term commitment; price-posting